Integrated Model of Culture, Information Technology, And Policy to Improve Lecturer Performance - Siti Syahsudarmi; Muhammad Rasyid Abdillah; Ririn Handayani; Arizal N. (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
This study examines the influence of organizational culture and information technology on institutional policies and lecturer performance in undergraduate Management study programs at private universities in Indonesia. It also explores the mediating role of institutional policies in the relationship between organizational culture, information technology, and lecturer performance. A quantitative descriptive survey approach was employed, with data collected via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The bootstrapping technique tested the significance of the construct relationships. Findings reveal that organizational culture and information technology significantly influence institutional policies and directly enhance lecturer performance. However, institutional policies do not significantly affect lecturer performance and do not mediate the relationship between organizational culture and information technology with lecturer performance. This study contributes original insights by integrating organizational culture, information technology, and institutional policy into a single model for analyzing lecturer performance.